Investment Decision and Market Value of Nigerian Listed Deposit Money Banks - Ajiboye, Oyewole Oladunni; Olagunju, Adebayo (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
This study considered the influence of investment decision on the market value of Nigerian listed deposit money banks (DMBs). Ex-post facto research design was employed. Secondary sources were used to gather information on market value and investment decisions. These sources included the annual reports of the banks that were sampled from 2010 to 2021. Out of the total population of 14 listed banks as of December 31, 2021, twelve (12) listed DMBs were chosen using the purposive sample technique. For data analysis, panel regression, correlation, and descriptive were tools employed. The outcome stated that return on capital employed recorded positive and significant influence on the Tobin Q and the market share price of listed Nigerian DMBs. The implication of the results is that banks that are able to generate better return on the capital employed in their operation have higher tendency to attract higher valuation in the market. It was concluded that investment decision served as determinant factors that influence the market valuation of Nigerian Deposit Money Banks. The study recommends that strategies to increase investment portfolio should be a priority; and also continue efforts should be made to improve return on capital employed that can enhance market valuation.